(untitled) (Agricultural Engineering, 2016)
The article presents the concept of the environmental management system. Moreover, organization frames of the undertaking related to eco-transport of waste were determined. Elements of the environmental management were characterized including the environmental aspect. They were subjected to interpretation in terms of reduction of the impact on the environment. In the context of constant improvement, the attention was paid to the influence of the analysed organization of its environmental activity. The objective of the paper is the analysis of assumptions which follow from the ISO 14001 standard including arrangement of the eco-transport of waste.